A pilot study on the effects of DHA/EPA-enriched phospholipids on aerobic and anaerobic exercises in mice. Issue 2 (23rd January 2020) - Wang, Cheng-Cheng; Ding, Lin; Zhang, Ling-Yu; Shi, Hao-Hao; Xue, Chang-Hu; Chi, Nai-Qiu; Yanagita, Teruyoshi; Zhang, Tian-Tian; Wang, Yu-Ming
Abstract : DHA/EPA-PL and l -carnitine had significant effects on aerobic exercise, while astaxanthin improved anaerobic exercise. The possible mechanism involved carbohydrate and lipid metabolism, mitochondrial respiratory chain and tricarboxylic acid cycle. Abstract : The beneficial effects of nonpolar DHA/EPA in triacylglycerol (TG) and ethyl ester (EE) forms as well as terrestrial phospholipids on physical fatigue have been widely reported. However, the results involving the effects were inconsistent, and the reason might be that the differences in physical fatigue induced by aerobic and anaerobic exercises were usually ignored. In addition, it has been reported the significant improvement of DHA/EPA esterified to phospholipids (DHA/EPA-PLs) on many fields but not physical fatigue. Therefore, the effects of DHA/EPA-PLs on physical fatigue induced by aerobic and anaerobic exercises were evaluated and compared with those of l -carnitine and astaxanthin using swimming and running exhaustion tests in mice, respectively. The results indicated that DHA/EPA-PLs and l -carnitine have significant effects on the performance of aerobic exercise, while astaxanthin had remarkable effects on the performance of anaerobic exercise. The possible underlying mechanisms indicated that DHA/EPA-PLs significantly promoted the carbohydrate and lipid metabolism as well as the mitochondrial respiratory chain and tricarboxylic acid cycle in muscles. The study presented a potential novel candidate or targeted dietary patterns for alleviating physical fatigue.